2018
DOI: 10.3389/fphar.2018.01218
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin and the Risk of Death, Stroke, and Major Bleeding in Patients With Atrial Fibrillation Receiving Hemodialysis: A Systematic Review and Meta-Analysis

Abstract: Background: Up to date, the efficacy and safety of warfarin treatment in atrial fibrillation patients receiving hemodialysis remain controversial. So we performed this meta-analysis to try to offer recommendations regarding warfarin management in this population.Methods: We searched Pubmed, Embase, and Cochrane library and reviewed relevant reference lists from 1980 to March 2018. Studies were included if they described the risks of mortality, stroke, and bleeding events with or without warfarin in atrial fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(69 reference statements)
2
3
0
Order By: Relevance
“…In the contemporary period, several meta-analyses have been performed in different parts of the world . With the latest studies, our data substantiate the results of these analyses, suggesting that there is no association between warfarin use for patients with ESRD and AF and protection against ischemic strokes but rather an association between warfarin use and a higher risk of hemorrhagic stroke .…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…In the contemporary period, several meta-analyses have been performed in different parts of the world . With the latest studies, our data substantiate the results of these analyses, suggesting that there is no association between warfarin use for patients with ESRD and AF and protection against ischemic strokes but rather an association between warfarin use and a higher risk of hemorrhagic stroke .…”
Section: Discussionsupporting
confidence: 80%
“…In the contemporary period, several meta-analyses have been performed in different parts of the world. 7,[24][25][26][27][28][29][30][31][32] With the latest studies, our data substantiate the results of these analyses, suggesting that there is no association between warfarin use for patients with ESRD and AF and protection against ischemic strokes but rather an association between warfarin use and a higher risk of hemorrhagic stroke. 15,[24][25][26]28 Lee et al, 26 Lui et al, 24 and Nochaiwong et al 27 showed that there was no association of warfarin use with ischemic stroke and mortality but that there was an association of warfarin use with an increased risk of hemorrhagic stroke and major bleeding.…”
Section: Comparison With Other Meta-analysessupporting
confidence: 86%
See 2 more Smart Citations
“…This was reflected in discordant recommendations, whereby one guideline did not recommend anticoagulant use for dialysis patients [47], and the other recommended warfarin but not new oral anticoagulants based on observational data [48]. However, the mortality benefit of warfarin in dialysis patients did not reach statistical significance in a meta-analysis of OSs [49]. In RCTs of anticoagulants, people with CKD and ESRD are frequently excluded [50,51].…”
Section: Discussionmentioning
confidence: 99%